Games and Learning Alliance 4th International Conference, GALA 2015, Rome, Italy, December 9-11, 2015, Revised Selected Papers - de Gloria, Alessandro; Veltkamp, Remco (Information Systems and Applications, incl. Internet/Web, and HCI, 2016)
This book constitutes the refereed proceedings of the 4th International Conference on Games and Learning Alliance, GALA 2015, held in Rome, Italy, in December 2015. The 33 revised full papers and 15 short papers presented were carefully reviewed and selected from 102 submissions. The papers presented cover a variety of aspects and knowledge fields. They are grouped around the following topics: games for health, games for mobility, pervasive gaming and urban mobility. .